Relationship between quantity of keratinized gingiva and periodontal health indexes in implant-supported fixed restorations. - Douine, Maylis; Bubom, Jean Jack; Ailincai, Rodica (Brazilian Journal of Implantology and Health Sciences, 2019)
Background: The effect of keratinized tissue width on the peri-implant health has not been well elucidated. The results of previous studies on this topic are controversial and the role of keratinized tissue width in the long-term success of dental implants has not been confirmed. This cross-sectional study aimed to assess the correlation of keratinized tissue width with periodontal indices around implant-supported fixed partial dentures (FPDs). Methods: This cross-sectional study evaluated 73 implants. Patients underwent periodontal examinations, including measurement of plaque index (PI), gingival index (GI), clinical probing depth (PD), bleeding on probing (BOP), marginal gingival recession, keratinized mucosa width and radiographic marginal bone level. Data were analyzed using SPSS. Results: The mean GI, PI and marginal gingival recession around implants with <2 mm width of keratinized gingiva were greater than the corresponding values around implants with keratinized tissue width of ≥2 mm. However, this difference was not statistically significant (P>0.05). No significant differences were noted in PD and radiographic marginal bone level between the two implant groups with keratinized tissue width <2 mm and ≥2 mm. Thus, no correlation was found between the keratinized tissue width and the measured indices. Conclusion: Although this study did not show a significant correlation between the keratinized tissue width and peri-implant tissue health and consequently the implant success rate, long-term interventional studies are required to make a final judgment in this respect.